Vaccines in the Treatment of Substance Abuse - Shorter, Daryl (2011)
Reconceptualizing drugs as toxins allowed an important shift in the approach to the treatment of substance abuse, because it ushered in consideration of immunological methods of pharmacotherapy. This paradigm shift represented a dramatic departure from previously considered approaches to pharmacotherapy for substance use disorders (SUDs), which had up until that time focused predominantly on either agonist and/or antagonist medications meant to block drug effects or to decrease reward, reinforcement, or craving. Use of immunological theory in SUD treatment also meant that 1) a potentially addicting medication would not be administered as part of therapy and 2) side effects could be limited, because the individual’s immune system would be responsible for delivering treatment.